![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
3个回答
展开全部
21. f(x) = 2x^2 + ax + 3, f(a) - f(a-1) = -17,
f(a) - f(a-1) = 2a^2 + a^2 + 3 - 2(a-1)^2 - a(a-1) - 3
= 2a^2 + a^2 - 2(a-1)^2 - a(a-1) = 5a - 2 = -17, a = -3
22. a > 1, a^(2x^2-3x+1) < a^(x^2+2x-5),
2x^2-3x+1 < x^2+2x-5, x^2 - 5x + 6 < 0
(x-2)(x-3) < 0, 2 < x < 3
f(a) - f(a-1) = 2a^2 + a^2 + 3 - 2(a-1)^2 - a(a-1) - 3
= 2a^2 + a^2 - 2(a-1)^2 - a(a-1) = 5a - 2 = -17, a = -3
22. a > 1, a^(2x^2-3x+1) < a^(x^2+2x-5),
2x^2-3x+1 < x^2+2x-5, x^2 - 5x + 6 < 0
(x-2)(x-3) < 0, 2 < x < 3
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询
广告 您可能关注的内容 |